Association between preoperative C-reactive protein and atrial fibrillation after off-pump coronary artery bypass grafting - Roy, Kaushik; Kamrul Hasan, M.; Raha, Sanjoy Kumar; Hoque, Al Masum Ziaul; Nahar, Arvi; Barua, Sumit; Parvez, Nayeem; Chowdhury, Nandita Sur (International Surgery Journal, 2026)
Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia and is associated with significant morbidity and mortality. This study aims to assess the association between preoperative C-reactive protein (CRP) levels and postoperative AF in Bangladeshi patients undergoing off-pump CABG. Methods: This comparative, cross-sectional study was conducted at the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases and Hospital (NICVD), Dhaka, Bangladesh, from July 2020 to June 2022, including 70 adult OPCAB patients divided by preoperative CRP levels (Group A: 0–<6 mg/l, Group B: 6–10 mg/l) to assess its association with postoperative atrial fibrillation. Standard preoperative evaluation, anesthesia, grafting and monitoring of intra- and postoperative events were performed, with data analyzed using SPSS-26 (p≤0.05). Results: Among 70 patients undergoing off-pump CABG, baseline demographic, clinical, laboratory and operative variables were comparable between groups (all p>0.05). Group A had significantly shorter ICU stay (3.71±0.96 vs 3.75±0.91 days, p=0.010) and hospital stay (8.94±2.96 vs 10.91±2.81 days, p=0.006). Postoperative atrial fibrillation occurred more frequently in Group B (40.0%) than Group A (11.4%) (p=0.006). Multivariable analysis identified preoperative CRP (6–10 mg/dl) as the sole independent predictor of postoperative AF (OR 6.32, p=0.006). Conclusions: Elevated preoperative CRP is an independent predictor of postoperative atrial fibrillation and prolonged ICU and hospital stay after off-pump CABG, highlighting its role in risk stratification and prevention.